Digital mapping of soil properties in the Center and West of Honduras, Central America - Martin López, Javier Mauricio; Silva, Mayesse Aparecida da; Valencia Gómez, Jefferson; Monserrate Rojas, Fredy Alexander; Leverón, Sindy; Quintero, Marcela (2021)
An update of the digital soil property maps for the West of Honduras (Da Silva et al., 2016), including now the center part of the country, was generated at 30 meters of spatial resolution to serve as input for the water-related analysis of the “Agua de Honduras” platform. The soil properties mapped presented in this repository are sand (%), silt (%), clay (%), texture class (USDA), and water holding capacity (mm).